The Proposed Merger of AT&T and T-Mobile: Are There Unexhausted Scale Economies in U.S. Mobile Telephony? - Russell Pittman (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2012)
From the beginning, the debate on the likely results of the proposed acquisition of T-Mobile USA by AT&T focused more on the claims of the parties that "immense" merger efficiencies would overwhelm any apparent losses of competition than on the presence or absence of those losses, and the factors that might affect them, such as market definition. The companies based their "economic model" of the merger on estimates of efficiencies on AT&T's "engineering model", without addressing the credibility of the results of the latter in the context of the economics literature on the telecommunications sector. In this paper we first argue that the economics literature on economies of scale (especially) and economies of density in mobile telephony suggests caution in expecting such massive cost reductions from increasing the size of an already very large firm. We then present new econometric evidence from an international data base supporting the notion that most large mobile telephone service providers have reached the point of constant or even (rarely) declining returns to scale.
Keywords: 330